2005
DOI: 10.1016/j.jacc.2005.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Versus Usual Care for Hospitalized Patients With Heart Failure

Abstract: The early application of UF for patients with CHF was feasible, well-tolerated, and resulted in significant weight loss and fluid removal. A larger trial is underway to determine the relative efficacy of UF versus standard care in acute decompensated heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(99 citation statements)
references
References 14 publications
1
96
0
2
Order By: Relevance
“…11,25 This may appear contradictory when compared with both diuretic and ultrafiltration trial results in which an increased diuretic-induced or ultrafiltration-induced volume loss was not accompanied by an improvement in morbidity and mortality. [25][26][27][28][29][30][31][32][33] Several possible explanations may be relevant. First, serial, in fact daily, assessment of filling pressures was made only in the IHM studies.…”
Section: Pathophysiologic Implications and Results Of Diuretic Trialsmentioning
confidence: 99%
“…11,25 This may appear contradictory when compared with both diuretic and ultrafiltration trial results in which an increased diuretic-induced or ultrafiltration-induced volume loss was not accompanied by an improvement in morbidity and mortality. [25][26][27][28][29][30][31][32][33] Several possible explanations may be relevant. First, serial, in fact daily, assessment of filling pressures was made only in the IHM studies.…”
Section: Pathophysiologic Implications and Results Of Diuretic Trialsmentioning
confidence: 99%
“…After independent screening for study inclusion, the full manuscripts or conference abstracts of 57 studies were reviewed and 10 were retained for final inclusion in the review. [3][4][5][6][8][9][10][11][12][13][14][15] A C C E P T E D M A N U S C R I P T…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated the efficacy of extracorporeal ultrafiltration compared to intravenous diuretics among decompensated patients without diuretic resistance and the results are inconsistent. [3][4][5][6] In view of the inconsistent evidence and the emergence of new studies we conducted a systematic review and meta-analysis to determine whether reported trials compared the efficacy of ultrafiltration with diuretics alone and if any patient groups more likely to benefit or be harmed by ultrafiltration compared to diuretics.…”
Section: Introductionmentioning
confidence: 99%
“…The first, Relief for Acutely Fluid Overloaded Patients with Decompensated Congestive Heart Failure (RAPID-CHF), was a proof of concept study of 40 patients with ADHF randomized to a single 8 hour period of UF or to usual care [63]. There was no significant difference between UF and usual care for the primary end point of weight loss at 24 hours, but fluid removal after 24 h was significantly greater with UF, with significantly improved dyspnea and HF symptoms at 48 h in the UF group.…”
Section: Ultrafiltrationmentioning
confidence: 99%